2005
DOI: 10.1103/physrevlett.95.205502
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical Simulation and Analysis of One-Dimensional Vibratory Sphere Packing

Abstract: We present a numerical method capable of reproducing the densification process from the so-called random loose to dense packing of uniform spheres under vertical vibration. The effects of vibration amplitude and frequency are quantified, and the random close packing is shown to be achieved only if both parameters are properly controlled. Two densification mechanisms are identified: pushing filling by which the contact between spheres is maintained and jumping filling by which the contact between particles is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(51 citation statements)
references
References 33 publications
4
46
1
Order By: Relevance
“…However, once the frequency is around 40 Hz, the number of particles with ordered structures increases sharply. Regarding to the previous study, ordered structure is not observed in a 1D vertically vibrated bed and ȡ is always not above 0.64 10 , which seems contradictory to the findings here. One difference between two studies is that the bottom is a mesh in this study, instead of flat plane in the previous study.…”
Section: Structure Of Final Statecontrasting
confidence: 56%
See 1 more Smart Citation
“…However, once the frequency is around 40 Hz, the number of particles with ordered structures increases sharply. Regarding to the previous study, ordered structure is not observed in a 1D vertically vibrated bed and ȡ is always not above 0.64 10 , which seems contradictory to the findings here. One difference between two studies is that the bottom is a mesh in this study, instead of flat plane in the previous study.…”
Section: Structure Of Final Statecontrasting
confidence: 56%
“…Any further increase in ȡ requires external energy to overcome the interparticle locking or jamming. One dimensional (1D) vibration can increase ȡ to 0.64 10 . Usually, packing of ȡ=0.64 is regarded as the maximally random jammed state (MRJ), which suggests that if ȡ is above 0.64, ordered structures will be formed in the packing 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there has been continual interest in the subject. Recent investigations (of which we list only a few) on density relaxation have involved computational approaches, theoretical models and physical experiments [1][2][3]9,10,16,18,24,25,29,30,34]. We remark that the study of waves in continuously vibrated granular systems has also been a topic of interest, as in [32] or the experiments of Eshuis et al [11] who developed a phase diagram delineating five physical regimes in a layer.…”
Section: Introductionmentioning
confidence: 95%
“…Here, we use DEM to generate initial packing structure before compaction and use MPFEM for compaction. DEM [23][24][25][26] and MPFEM [18,27] simulation methods in corresponding processes have been successfully utilized in our previous work, therefore, the details of these methods will not be illustrated here. Readers who are interested please refer to our recently published papers.…”
Section: Simulation Methodsmentioning
confidence: 99%